Glyptic Treasures in Krakow and Old Master Paintings Collection of Constantine Schmidt-Ciążyński .......... 99 - Gołyźniak, Paweł (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
This article is based on two lectures delivered during the symposium “Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century” held at the University of Wrocław, 25–26 March 2021. It discusses two collections related to the glyptic art housed in Krakow: a pictorial archive once owned by Philipp von Stosch including visual reproductions of his own gems as well as those from other contemporary cabinets, now in the Princes Czartoryski Museum in Krakow and the Constantine Schmidt-Ciążyński collection of engraved gems in the National Museum in Krakow. These two different sets enable us to illustrate the history of collecting intaglios and cameos, and explain why engraved gems became such a popular phenomenon among the eighteenth and nineteenth century enthusiasts of antiquity, its art and craftsmanship. In addition, Constantine Schmidt-Ciążyński’s collection of Old Master paintings is briefly discussed as another proof of his extraordinary connoisseurship and taste.